Personality and Charismatic Leadership in Context: The Moderating Role of Situational Stress. Issue 1 (19th February 2014) - Oreg, Shaul; Berson, Yair
<x xml:space="preserve">Abstract</x> We adopt an interactionist perspective and extend previous work on personality and charismatic leadership by considering the relationship between them across contexts. Based on Gray's reinforcement sensitivity theory, we expected the relationships between approach‐oriented dispositions and charisma to diminish under conditions of high workload‐induced stress. In a large‐scale lab study with 201 groups (Study 1, N = 721 participants), we manipulated conditions of stress and tested the interaction of stress with leaders' extraversion and openness to experience in predicting their charismatic behaviors. We then tested, in a field study of 71 executives (Study 2, N = 256 participants), the interaction of employees' reported stress with leaders' stimulation values in predicting their charismatic behavior. In support of our hypotheses, the relationships between approach‐oriented dispositions and charisma were significantly weaker when stress was high. We discuss theoretical and practical implications of this finding, in particular given that it is in stressful conditions under which charismatic leadership is said to be most important.